Risk based meat safety assurance system – An introduction to key concepts for future training of official veterinarians - Mojsova, Sandra; Ferri, Maurizio; Blagojevic Bojan; Maurer, Patric; Hengl, Brigita; Guldimann, Claudia; Sakaradis, Ioannis; Antunovci, Boris; Gomes-Neves, Eduarda; Zdolec, Nevijo; Vieira-Pinot, Madalena (Elsevier, 2022)
More than a decade ago, the European Food Safety Authority (EFSA) sparked a substantial modernisation effort in traditional meat safety systems in Europe by publishing a range of EFSA opinions that were followed, from 2014 to 2019, by amendments to relevant EU legislation. A novel, risk-based meat safety assurance system (RBMSAS) was proposed to address the latest, most relevant meat-borne hazards and protect human health as well as animal health and welfare. This new framework was thought to offer substantial advantages with regard to the combination and longitudinal integration of prevention and control measures along the meat production chain. Official veterinarians (OVs) are expected to take on a central role as risk managers in RB-MSAS and will benefit from the use of harmonised epidemiological indicators (HEIs) and food chain information (FCI). In this article, we aim to provide an introduction to the key concepts of RB-MSAS and elaborate on the potential training needs of OVs as key risk managers in this novel framework. To this end, we present an overview of the components of an RB-MSAS along with the main factors that may hamper its development vis-a-vis ` the current status of the European meat inspection system. We state key future challenges related to the conceptual and practical implementation of a RB-MSAS and give potential solutions. In addition, the technical description of the HEIs proposed by EFSA for different animal species and at specific stages of the food chain is provided, as is their use to categorise farms and abattoirs according to the risk and to conduct risk-based meat inspection. Finally, advanced training tools for OVs enabling them to effectively and efficiently operate as risk managers in the future RB-MSAS environment are outlined.
Keywords: Risk-based meat inspection; Official veterinarians; Harmonised epidemiological indicator; Food chain information; Training